Factors affecting purchase intention toward organic cosmetic products among consumers in the Klang Valley, Malaysia - Mohd Ali, Ainunnazlee (2013)
The cosmetics industry has dramatically diversified its business orientation from conventional to organic in order to fulfil consumer‟s needs and demands. The present study explored the influence of attitude, subjective norms, perceived behavioural control and trust in predicting intention to purchase organic cosmetic products. A cross-sectional research design using survey technique was conducted among 400 consumers in the Klang Valley using mall-intercept survey. The main reason for using organic cosmetic products was health (81.1%). Respondents used organic cosmetic products then purchased mostly at pharmacy (65.6%) and personal care store (39.6%). All the factors examined in Theory Planned Behaviour namely attitude towards the behaviour (r=0.0285,p≤0.01), attitude towards organic cosmetic products (r=0.249, p≤0.01),subjective norms (r=0.283, p≤0.01), perceived behaviour control (r=0.419,p≤0.01) and an added factor is trust (r=0.049, p≤0.01), had significant relationship with intention to purchase with various strength. However, only trust and perceived behaviour control contributed significantly to predicting consumers‟ purchase intention with adjusted R2=0.271, F (4,395) = 38.096,p≤0.001. The model explained 27.1% of the variance with trust having the most predictive power. Therefore, genuine information has to be provided such as organic certification if adaption of organic cosmetic product is to be enhanced as organic cosmetic products are good for both environment and health.